Law and National Environmental Policy: The challenges faced today in Brazil (2019-2021) (Research, Society and Development, 2022)
A This article aims to present the environmental policies provided for in this agreement. As a research method, a bibliographic survey was used on academic research sites, as well as reports in widely circulated newspapers. First, a brief history of negotiation regarding environmental policies will be made. Afterwards, a normative legal analysis of the text of the agreement is carried out, specifically with regard to the chapter on sustainable development, in free translation of the original text. Finally, a brief conclusion on the obstacles to the effectiveness of this agreement in relation to the environmental policies that have been used by the Ministry of the Environment, of the Federal Government since 2020, after the publication of the draft. This article objectively shows the emergence of Law 6,938 of 1981 of the National Environmental Policy (PNMA) which completed 40 years of validity in 2021, being a historic milestone in the country's environmental management and the challenges faced over time to achieve sustainable development. The article seeks to answer the following question, what are the challenges faced by the national environmental policy at the federal level between the years 2019 to 2021? The method used was the bibliographic analysis and presentation of quantitative and qualitative data from secondary research, developed in the period by organized civil society institutions that monitor environmental policies. We seek to illustrate the performance by pointing out recent events that have contributed to a worsening of environmental indicators in Brazil and to the (re)emergence of environmental problems. The article is divided into two parts, the first deals with the normative legal issue, presenting the meaning of Law 6.938/81, its pioneering spirit and contribution in the pursuit of sustainable development and the guarantee of the diffuse right to the environment in Brazil. In the second moment, data regarding the performance of federal environmental policies in the period 2019-2021 are presented, especially with regard to transparency and popular participation, including the management of the current government. Finally, the article makes succinct notes on the directions of environmental policies, seeking to encourage discussion on the subject.